2019
DOI: 10.1002/ejhf.1461
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure in cardiomyopathies: a position paper from the Heart Failure Association of the European Society of Cardiology

Abstract: Cardiomyopathies are a heterogeneous group of heart muscle diseases and an important cause of heart failure (HF). Current knowledge on incidence, pathophysiology and natural history of HF in cardiomyopathies is limited, and distinct features of their therapeutic responses have not been systematically addressed. Therefore, this position paper focuses on epidemiology, pathophysiology, natural history and latest developments in treatment of HF in patients with dilated (DCM), hypertrophic (HCM) and restrictive (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
243
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 287 publications
(302 citation statements)
references
References 248 publications
3
243
0
6
Order By: Relevance
“…Moreover, ventricular hypertrophy primarily triggered by arterial hypertension might add to this shortage [4]. Nevertheless, former studies have also shown a considerable prevalence of storage diseases such as amyloidosis and Morbus Fabry resulting in HFpEF [24]. Additionally, also an impairment in coronary microcirculation by means of coronary microvascular endothelial inflammation increasing resting tension through a reduction in nitric oxide bioavailability, cyclic guanosine monophosphate content and protein kinase G (PKG) activity found in HFpEF patients contributes to a shortage in myocardial oxygen supply [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ventricular hypertrophy primarily triggered by arterial hypertension might add to this shortage [4]. Nevertheless, former studies have also shown a considerable prevalence of storage diseases such as amyloidosis and Morbus Fabry resulting in HFpEF [24]. Additionally, also an impairment in coronary microcirculation by means of coronary microvascular endothelial inflammation increasing resting tension through a reduction in nitric oxide bioavailability, cyclic guanosine monophosphate content and protein kinase G (PKG) activity found in HFpEF patients contributes to a shortage in myocardial oxygen supply [25].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with symptomatic oHCM are generally offered first‐line pharmacotherapy with β‐blockers or the non‐dihydropyridine calcium‐channel blockers . Disopyramide is effective as an add‐on therapy, although it can be poorly tolerated.…”
Section: Novel Pharmacotherapies For Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…The two most common types of cardiac amyloidosis are transthyretin (TTR)-related and light-chain amyloidosis (AL). 22 Milandri et al 23 evaluated the prevalence and impact of carpal tunnel syndrome (CTS) in patients with TTR and AL amyloidosis, compared to the general population. CTS was most common in male, elderly patients with TTR amyloidosis and cardiac involvement.…”
Section: Cardiac Amyloidosismentioning
confidence: 99%